Hubungan Kualitas Pelayanan Terhadap Kepuasan Pasien BPJS Rawat Inap RSUD Batara Guru Tahun 2024 - Assyahra, Sabrina; A. Multazam Mustari; A. Rizki Amelia AP (Window of Public Health Journal, 2025)
Service Quality is the best service carried out by a person, group, or institution that satisfies customers or the community. In turn, that satisfaction will create customer or community loyalty to a person/group/institution that provides the service. The effectiveness of quality is determined by customer satisfaction, which will meet the desired needs of the parties involved to ensure the quality of service is by rapid developments. This study aimed to determine the relationship between service quality and inpatient BPJS patients at Batara Guru Hospital, Luwu Regency, in 2024. The method used is a quantitative cross-sectional approach method. The sample of this study was inpatient BPJS patients at Batara Guru Hospital, which had a population of 312 patients and a sample size of 90 patients, as determined by the Slovin formula. The research results show that there is a relationship between the quality of Service to BPJS Inpatient Patients based on physical evidence (tangible) (p = 0.001), reliability (p = 0.001), Responsiveness (p = 0.001), Empathy (p = 0.001), and assurance (p = 0.001). The advice given to the Hospital is expected to make improvements, enhancements, and development of physical facilities so that patients and their families feel comfortable.